The diagnostic value of endometrial thickness and volume measurements by transvaginal three-dimensional ultrasound in patients with perimenopausal bleeding - Atia, Naira A.; El Namoury, Mohamed M.; Farhat, Manal A.; Hamouda, Mahmoud S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Endometrial hyperplasia (EH) represents a spectrum of irregular morphological alterations, whereby abnormal proliferation of the endometrial gland results in increased thickness of endometrial tissue with alterations of glandular architecture (shape and size) and in an increase in gland-to-stroma ratio when compared to endometrium from the proliferative phase pf the cycle. The aim of this study was to detect the role of measurement of endometrial thickness and volume by transvaginal three-dimensional ultrasound as predictors of abnormal endometrial pathology in women with peri menopausal abnormal uterine bleeding. Methods: This study was conducted at the department of obstetrics and gynecology of Tanta University Hospital. The cases were selected from admitted patient suffering from perimenopausal uterine bleeding. The study started after protocol approval from 2020 to 2022. The calculated sample size was 50 cases. The studied cases were subjected to 3D-TVS measuring endometrial volume and endometrial thickness, study uterine size, shape, endometrial curettage and histopathological examination. Results: Regarding provisional diagnosis by ultrasound in the examined patients, the most frequent diagnosis was benign endometrial pathology: 46% (n=23) of all cases then endometrial hyperplasia 44% (n=22) then endometrial carcinoma 10% (n=5), there was statistically significant difference between the three endometrial pathologies regarding endometrial thickness (p˂0.001), and endometrial volume (p˂0.001).There was statistically significant difference between the benign endometrial pathology and endometrial carcinoma regarding endometrial thickness (p˂0.001), and endometrial volume (p˂0.001).There was statistically significant difference between the endometrial hyperplasia and endometrial carcinoma regarding endometrial thickness (p˂0.001), and endometrial volume (p˂0.001). Conclusions: From our study we conclude that histopathological examination of the endometrium is the gold standard for diagnosis or exclusion of endometrial pathology. 3D ultrasound is a reasonably accurate, helpful, and non-invasive tool for assessing the endometrium.